A multipurpose dressing: role of a Hydrofiber foam dressing in managing wound exudate. (1st September 2019) - Walker, Angela; Brace, Jacalyn
Abstract : Chronic wound exudate is associated with stalled or delayed healing. Excess amounts will break down healthy tissue, increasing the production of slough and necrotic tissue. This will also create an ideal environment for microbial proliferation and place the surrounding skin at risk of maceration. It is vital, therefore, to select an absorbent dressing that can retain excessive exudate. This article describes how to achieve this. It introduces an absorbent dressing, Aquacel Foam, which not only retains exudate, but can also help remove devitalised tissue and promote healing